Answer:
See below ~
Step-by-step explanation:
Given :
⇒ m∠1 = m∠2
⇒ HD = GF
=============================================================
To Prove :
<u>Δ EHD ≅ Δ EGF</u>
<u />
============================================================
Solving :
⇒ m∠1 = m∠2 (Given)
⇒ HD = GF (Given)
⇒ ∠E = ∠E (Common angle)
⇒ ΔEHD ≅ ΔEGF (AAS congruence)
I uploaded the answer t
o a file hosting. Here's link:
bit.
ly/3tZxaCQ
Answer:
1x+46 is the answer
Step-by-step explanation:
=4(-8x + 5) – (-33x – 26)
opening brackets to simplify
=-32x+20+33x+26
=-32x+33x+20+26
=1x+46 is the answer
hope it will help :)
Answer:
B. -1/3
Step-by-step explanation:
replace <em>x</em> with 34 and solve it.